2017
DOI: 10.1007/s41669-017-0051-2
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Clinical and Economic Value of Primary Tumour Identification in Metastatic Cancer of Unknown Primary Tumour: A Population-Based Retrospective Matched Cohort Study

Abstract: PurposeSeveral genomic tests have recently been developed to identify the primary tumour in cancer of unknown primary tumour (CUP). However, the value of identifying the primary tumour in clinical practice for CUP patients remains questionable and difficult to prove in randomized trials.ObjectiveWe aimed to assess the clinical and economic value of primary tumour identification in CUP using a retrospective matched cohort study.MethodsWe used the Manitoba Cancer Registry to identify all patients initially diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Few studies have documented the costs of CUP during the diagnosis phase. In a Canadian study, healthcare costs were significantly higher 6 months prior to diagnosis across most resource types in those with CUP compared with a mixed and matched sample of patients with known primary cancers, yet treatment costs after diagnosis were lower [ 6 ]. Our findings contradict these results in the treatment phase where cancer therapy costs appear to be higher and MBS costs similar for CUP patients (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have documented the costs of CUP during the diagnosis phase. In a Canadian study, healthcare costs were significantly higher 6 months prior to diagnosis across most resource types in those with CUP compared with a mixed and matched sample of patients with known primary cancers, yet treatment costs after diagnosis were lower [ 6 ]. Our findings contradict these results in the treatment phase where cancer therapy costs appear to be higher and MBS costs similar for CUP patients (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings contradict these results in the treatment phase where cancer therapy costs appear to be higher and MBS costs similar for CUP patients (Table 2 ). However, our study compared patients with CUP to women with ovarian cancer, with all patients having stage III or IV disease, unlike the mixed cancer sample used in the Hannouf et al (2018) study [ 6 ]. Australian studies in older patients with CUP have shown higher use of general practitioner consultations, palliative care services, hospitalisations and emergency department visits 3 months before and after diagnosis, compared with metastatic cancer of known primary site [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Patients with CUP are often treated with empiric chemotherapies such as taxanes and platinum-containing regimens. 3,4 Median overall survival (OS) remains dismal, ranging from 6 to 15 months. [5][6][7][8][9] Initial work-up, as recommended by the National Comprehensive Cancer Network guidelines, includes a history and physical examination, basic laboratory tests, computed tomography scans, clinically directed endoscopy, and microsatellite instability/mismatch repair gene testing.…”
Section: Introductionmentioning
confidence: 99%